EVIDENCE OF RIFT MAGMATISM FROM PRELIMINARY PETROLOGICAL DATA ON LOWER TRIASSIC MAFIC ROCKS FROM THE NORTH DOBROGEA OROGEN (ROMANIA) - Saccani, Emilio; Seghedi, Antoneta; Nicolae, Ionel (Ofioliti, 2004)
The Cimmerian orogenic belt of North Dobrogea (East Romania) is located in the Carpathian foreland between the Moesian and Scythian Platforms. In the absence of reliable geochemical data on the different magmatic rock-types, various geodynamic models have been suggested for the Triassic-Jurassic evolution of this belt. Geochemical studies on mafic dykes emplaced in different Hercynian basement rocks, as well as on the Early-Middle Triassic Niculitel Formation basalts have been performed in order to provide new constraints for the geotectonic setting of this belt. A Permo-Triassic phase of crustal thinning of the Hercynian basement is suggested by the still poorly known alkaline magmatism. The Triassic magmatic history involves intrusion of tholeiitic dykes in the Hercynian basement of the Macin Zone, and extrusion of pillow basalts (Niculitel Formation) that most likely occurred above the carbonate compensation depth in a rifted basin with a thinned crust, as suggested by facies characteristics of carbonate rocks interbedded with basalts. This basin could have corresponded either to an aborted rift, or to a passive margin related to back-arc opening. Our data indicate that Macin and Niculitel basalts are derived from a MORB-type asthenospheric mantle source variably influenced by a plume-type component. The less enriched character of the Macin dykes reflects a lesser influence of plume source on magma composition with respect to the Niculitel basalts. Modern chemical analogues are found in the South West Indian and American-Antarctic Ridges, where composition of basalts range from pure plume-type ocean island basalts (OIBs) to pure MORBs, depending on the influence of the Bouvet mantle plume on MORB source. Regardless of the geochemical differences, which can reasonably be related to local variations of the plume component influence on the MORB source, a common geodynamic setting can be postulated for the origin of the two basaltic series. In the hypothesis of the aborted rift, an evolution of the mantle sources, starting with a predominating plume activity followed by an uprise of the primitive asthenospheric mantle, can be postulated for the North Dobrogea Triassic basalts. By contrast, in the back-arc basin model, the plume activity may have played a major role in weakening the lithosphere and preparing the back-arc spreading. The close geochemical similarities between basalts from North Dobrogea and basalts from various ophiolitic complexes and oceanic ridges do not necessarily imply that North Dobrogea Triassic basalts represent an ophiolitic sequence or, in other words, the hypothesized uprise of asthenospheric primitive mantle does not imply an oceanic spreading steady-state. Our data indicate that the Macin and Niculitel basalts originated in an extensional tectonic setting in which the transition from alkaline to E-MORB magmatism was a consequence of the mantle plume evolution through time.